1967
DOI: 10.1021/jf60151a028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recovered natural orange flavor enhancement materials using gas chromatography

Abstract: New information is presented concerning the chemistry of flavor relative to the processing of orange juices. Capillary column-flame ioniza-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 11 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…The results of the further identification experiments (Table ) showed that 45 out of the 51 odorants detected by GC/Olfactometry could be identified. In general, the results confirmed data of previous studies ,,,,, aimed at identifying either volatile or odor-active compounds in orange juices of different origins and varieties. However, 2-ethyl-3- and 2-ethyl-5-methylpyrazine ( 16 ) and 3-hydroxy-4,5-dimethyl-2­(5 H ) furanone ( 46 ) are reported here as additional odorants in orange juice, although both showed only low FD factors.…”
Section: Resultssupporting
confidence: 89%
“…The results of the further identification experiments (Table ) showed that 45 out of the 51 odorants detected by GC/Olfactometry could be identified. In general, the results confirmed data of previous studies ,,,,, aimed at identifying either volatile or odor-active compounds in orange juices of different origins and varieties. However, 2-ethyl-3- and 2-ethyl-5-methylpyrazine ( 16 ) and 3-hydroxy-4,5-dimethyl-2­(5 H ) furanone ( 46 ) are reported here as additional odorants in orange juice, although both showed only low FD factors.…”
Section: Resultssupporting
confidence: 89%
“…This analysis was undertaken in order to determine if significant amounts of the volatile compounds characteristic of orange essence were present in the oil. Ethyl butyrate was the only major component in essence oils which had been commonly observed in the orange essences (Teranishi et al, 1966 andWolford et al, 1967), but not in coldpressed orange oils. The presence of this compound in the oil can be explained as the result of the partitioning of volatile essence components between the aqueous essence phase and the oil phase.…”
Section: Separation Proceduresmentioning
confidence: 97%
“…46 The volatile flavor components in recovered orange essence are listed in Table 9. 11 Besides those in Table 9, other reported volatiles of orange essence include: l-penten-3-ol, methyl butyrate, methyl hexanoate, benzaldehyde, and y-decanolactone. 39 Minor essence components more recently reported include 1,1-ethoxymethoxyethane, ethyl vinyl ketone, trans 2-pentenal, heptanol c/s-2,8-p-menthadiene-l-ol, cis carveol, and piperitenone.…”
Section: Orange Essencementioning
confidence: 99%